The beauty of romance and religious thought in Hamka's novels - Qaziah Fatihah Berhanuddin; Mohammad Affiq Kamarul Azlan; Irfan Saumi (2015)
Have we ever imagined the world without love? In any field, approach and culture, people will talk about love and the importance of feeling the sense of belonging. Every religion either, promotes love. In such areas as religious preaching in Islam, the term “love” mostly used to relate mankind with God. Nonetheless, it is rare to find a prominent scholar to describe or write about love of a romantic relationship between a man and a woman before the marriage contract been signed. It is neither the essential context nor the substantial significance, rather, it is regarded as a serious issue in Muslim community. Hence, the creative writing of this thematic relationship is apparently isolated. Ironically, this was among the remarkable works of Hamka, a well-known prominent Nusantara Muslim scholar in the early twentieth century. In his famous novel Di Bawah Lindungan Ka’bah, Hamka portrayed an Islamic theme on the absolute title, but he made a very different atmosphere in the contents of the whole dramatic novel. On the other hand, he had cynically criticized the tradition of Minangkabau in his splendorous romantic novels Tenggelamnya Kapal Van Der Wijck, and Merantau Ke Deli. Here, there are some questions to be pointed out, is it an Islamic acceptance by an-attempt of advising Muslim societies through a romantic writing? Instead of politely criticizing the traditions of his people, are there other purposes in his creative writings? How can the Muslim communities, in specific, accept the ideas of dakwah in this clash style?